An in silico approach for the identification of clinically significant SNPs in a Drug Metabolizing Gene CYP2C9 and development of Tetra-primer ARMS PCR based genotyping method for CYP2C9*3 (rs1057910) - Ahmed, Rifaquat (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology 2020.